The impact of the coronavirus crisis on the market price of risk - Delis, Manthos D.; Savva, Christos S.; Theodossiou, Panayiotis (My University, 2021)
We study an equilibrium risk and return model to explore the effects of the coronavirus crisis and associated skewness on the market price of risk. We derive the moment and equilibrium equations, specifying skewness price of risk as an additive component of the effect of variance on mean expected return. We estimate our model using the flexible skewed generalized error distribution, for which we derive the distribution of returns and the likelihood function. Using S&P 500 Index returns from January 1980 to mid-October 2020, our results show that the coronavirus crisis generated a deeply negative reaction in the skewness and total market price of risk, more negative even than the subprime and the October 1987 crises.
Keywords: Finance; Asset pricing; Risk and return; Skewness; Financial instability; Coronavirus crisis; Subprime crisis